ANALISIS PREFERENSI INVESTOR TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI - Meryna Rachmi Putri; Anik Malikah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this research is to determine the effect of motivation, knowledge, return, risk and minimal capital on investment decision making in the capital market. This research is a survey research which is a quantitative method in the form of primary data. The population of this study were students of the Faculty of Economics and Business, Malang 2016 Islamic University Force class of 2016 and 2017. The sampling technique used simple random sampling and the determination of sample size using Slovin formula. The sample used was 228 respondents, but the sample that could be processed was 200 respondents obtained through data collection methods by distributing questionnaires measured using a Likert scale. This study uses multiple linear regression analysis methods, descriptive statistical tests, data quality tests, normality tests, classic assumption tests, and hypothesis testing with the help of SPSS 16.0. The results of this study indicate that simultaneous motivation, knowledge, return, risk and capital minimally influence investment decision making. Motivation, return, and minimal capital have a partially positive effect on investment decision making. Knowledge and risk does not have a partially effect on investment decision making. Keywords: investor preferences, motivation, knowledge, return, risk, minimal capital and investment decision making.